CHARACTERIZATION OF TRAFFIC-RELATED AIR POLLUTANTS AND ASSESSMENT OF RESPIRATORY CONDITIONS OF TRAFFIC WARDENS ACROSS TWO SELECTED LOCAL GOVERNMENT AREAS OF IBADAN, NIGERIA. (2013)
Traffic-related emissions contribute immensely to ambient air pollution in urban areas and Traffic Wardens (TW) have been reported to be at high risk of respiratory problems. Although data on road traffic emissions are available in Nigeria, information on personal exposure of traffic wardens to particulate matter is lacking. This study was designed to characterize traffic emissions and compare lung function status of TW with Regular Policemen (RP) in two Local Government Areas (LGA) of Ibadan. A comparative cross-sectional study was conducted involving all 122 TW (exposed group) in the study area and 125 RP (unexposed group). Ibadan North and Northeast LGAs were purposely selected based on high traffic density. Thirteen Study Locations (SL) were randomly chosen from eighteen identified SL in the two LGAs. Levels of sulphur dioxide (SO2), nitrogen dioxide (NO2) and carbon (II) oxide (CO) emissions were measured using calibrated SO2, NO2 and CO metre respectively according to WHO guideline. Respirable Suspended Particulate Matter (RSPM) was measured using personal respirable dust sampler within 30cm range of the TW nasal region and values were compared with WHO guideline limit. Measurements were taken in the morning (6am - 8am), afternoon (12pm - 2pm) and evening (4pm - 6pm) for 12 weeks. Traffic density was estimated via manual counting using tally system. An interviewer-administered questionnaire was used to elicit information from the 247 respondents on work hours and respiratory problems. A calibrated spirometer was used to determine the Force Expiratory Volume in 1 second (FEV1) in 61 of the 122(TW) and 63 of the 125RP. Data were analyzed using descriptive statistics, Chi-square and Pearson correlation tests at p ≤ 0.05. Mean gaseous emissions level were CO (38.6 ± 22.2ppm), SO2 (1.0 ± 0.7ppm), NO2 (0.2 ± 0.1ppm) and RSPM (28.1 ± 11.5µg/m3). These values exceeded the WHO guideline limit for CO (10ppm), SO2 (0.17ppm), NO2 (0.17ppm) and RSPM (25µg/m3). The peak CO emission level (165ppm) was recorded in the evening (4pm-6pm). Mean total traffic density at the SL was 3478 ± 1043.4/hr. Mean concentration of traffic emissions were elevated with increase in traffic density at SL. There was a significant positive correlation between SO2 and traffic density (r= 0.48). Mean age of TW and RP were 37.7 ± 9.3 years and 37.0 ± 7.7 years respectively. Majority (54.9%) of the TW spend more than 8hours at road intersections. Reported respiratory problems experienced included: breathing difficulty (TW: 66.4%; RP 6.4%), chest pain (TW: 72.1%; RP: 5.6%), sore throat (TW: 60.7%; RP: 14.4%) and catarrh (TW: 68.9%; RP: 41.6%). There was a significant difference between the observed FEV1 among TW (2.2 ± 0.7l) and RP (3.4 ± 0.5l). A negative correlation was observed between RSPM and the actual FEV1 of TW (r= -0.6). Ambient air emissions at study locations exceeded the World Health Organization guideline limit for occupational exposures and respiratory problems were higher among traffic wardens. Routine air monitoring of motor ways and the use of personal protective equipment by traffic wardens while on duty is advocated.